New electro-active paper actuator using conducting polypyrrole: actuation behaviour in LiClO(4) acetonitrile solution - Deshpande, S. D.; Kim, Jaehwan; Yun, S. R. (Synthetic Metals, 2005)
The construction of electromechanical actuator has been achieved by using the conducting polypyrrole films deposition onto a gold-coated cellophane paper. This is probably the first report of this type of paper actuator. The conducting polypyrrole was electro-generated using either galvanostatic or potentiostatic conditions at 0.5 mA/cm(2) current density or 0.7 V applied potential, respectively. The two types of actuators were constructed, namely: (1) Ppy/cellophane bi-layer; (2) Ppy/cellophane paper/Ppy tri-layer. These actuators showed a reversible and reproducible displacement in acetonitrile solution containing LiClO(4) (I M). The maximum displacement of 9.1 mm was recorded for tri-layer device and 3.5 mm for bi-layer device in 1 M LiClO(4) acetonitrile solutions. The results obtained in acetonitrile solution containing 1 M LiClO(4) shows that the actuator requires very low excitation voltage of 0.2 MV m(-1). The mechanism for this paper actuation phenomenon is addressed in this paper. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CP-EAPap actuators; electro-active paper actuator (EAPap); large displacement actuators; lightweight actuators; Ppy/cellophane paper bi-layer; Ppy/cellophane paper/Ppy tri-layer